Oral lesions of systemic lupus erythematosus: A collaborative Latin American study - de Arruda, José Alcides Almeida; Villarroel-Dorrego, Mariana; Freire, Clara Herrera; Molina-Ávila, Ignacio; Pimentel-Solá, Juan Martin; Gilligan, Gerardo; Piemonte, Eduardo; Panico, René; Panico, Juan Cruz Romero; Aranda-Romo, Saray; Tejeda-Nava, Francisco Javier; Israel, Mônica Simões; et al. (SAGE Publications, 2024)
Background: Systemic lupus erythematosus (SLE) is a multifactorial autoimmune disease that may affect the oral mucosa. The variable spectrum of oral lesions observed in SLE can pose challenges in diagnosis, particularly when the lesions occur in isolation. The aim of this study was to describe the oral lesions occurring in patients with SLE from Latin America. Methods: This collaborative record-based study involving 11 oral and maxillofacial pathology and medicine services across Venezuela, Argentina, Chile, Brazil, and Mexico describes the clinicopathological profile of SLE-related oral lesions. Results: Seventy patients with SLE and oral lesions were included in the study. The majority were females (75.7%; female/male ratio: 3.1:1) and white (62.1%), with a mean age of 38.4 years (range: 11–77 years). The most common site of oral lesions was the hard/soft palate (32.0%). Clinically, oral lesions predominantly presented as ulcers (26.6%), erosions (26.6%), and white lesions (23.4%). Isolated oral lesions occurred in 65.2% of individuals, while cutaneous manifestations occurred in 80.3%. The main clinical diagnostic hypothesis in 71.4% of cases was an immune-mediated disease. Oral biopsies followed by histopathological analysis were performed in 50 cases. Conclusion: Oral lesions of SLE exhibit a variety of clinical and histopathological features. A key point in diagnosis is that unusual oral changes without an obvious local cause may indicate a possible systemic condition presenting with oral lesions. A multidisciplinary approach, which includes regular oral examination, is warranted to identify oral lesions and provide treatment.
Keywords: Autoimmune disease; differential diagnosis; Latin America; oral mucosa; systemic lupus erythematosus